Los Mercados Municipales como Actores e Impulsores del Modelo de Desarrollo Local en la Ciudad de Riobamba - Vallejo Tixi, María del Carmen (2022)
ABSTRACT: The present research work is carried out due to the need to determine the effect of the participation of Municipal markets as actors and promoters of the local development model in the city of Riobamba, through the use of direct observation and the applied survey, real information was obtained by part of the merchants of the different markets, whose result obtained from them allows it to be necessary to develop a proposal, not only for internal improvement of the different markets but also based on being an important element in the local development of the town. The work is made up of five chapters which are developed as follows: CHAPTER I: Where you can see the introduction, planting of the problem, and its formulation, as well as the Justification, Objectives, and Hypotheses. CHAPTER II: In this chapter the theoretical framework is developed, where there are definitions of several authors about Local Development, history, Characteristics, Components, Importance, in the same way, Market definition according to several authors, history, characteristics, an important role of Municipal Markets economic and social function, the markets as a new bet of tourist attraction for the city, Municipal markets of Riobamba. CHAPTER III: The methodology, the type of research, the research design, the population and the sample, research methods, techniques and instruments for data collection, techniques and instruments for the analysis of results are presented. CHAPTER IV: The analysis of the results obtained in the surveys carried out to the merchants of the different markets of the city of Riobamba on aspects such as: if the infrastructure of the market should be improved for better attention to the user, if there are adequate spaces for the collection of waste if the market has a positive influence on the development of the sector, etc. The hypothesis is verified. The conclusions and recommendations are structured. CHAPTER V: The proposal is made in which you have the Title, Introduction, Background, Problematic, Objectives, Development, Internal and external analysis of the municipal markets of the city of Riobamba. KEYWORDS: Municipal Markets, Local Development, Tourism, Commerce, Innovation.